Public Debt Sustainability: The Case of Greece - Tantos, Stefanos (Journal of Reviews on Global Economics, 2012)
Abstract: The purpose of this study is to examine whether the Greek public debt will be sustainable up to 2020. To this end, we develop a debt sustainability model and carry out an empirical investigation based on a system of four equations for the period 1980-2009. By conducting a number of simulations, we find that the change of public debt to GDP ratio decreases when the primary deficit decreases or the growth rate increases, while this ratio rises when the real interest rate increases. Finally, adopting scenarios of public debt sustainability for the period 2013-2020, we find out that the debt can be sustainable in the case of high primary surpluses or high growth rates. However, surpluses and growth rates may be lower if the revenues from privatizations or an additional haircut are introduced into the analysis.